The insulin sensitivity of non-obese Malay subjects and the relationship between hyperlipidemia with insulin sensitivity - Hassan, Mohd Hashim Mohd; Al-Mahmood, Abu Kholdun (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Introduction: Hyperlipidaemia and insulin resistance may have a relationship. Most of the previous studies looked at insulin resistance in hyperlipidaemic subjects who were also obese. So influence of obesity and hyperlipidaemia acted simultaneously in the genesis of insulin resistance. Objective: To determine insulin sensitivity and secretory status of non-obese normoglycemic Malay subjects, and to study the relationship between hyperlipidemia and insulin sensitivity in such population. Methodology: A cross sectional study on 246 non-obese (BMI<25kg/m2 , waist circumference male<102cm, female <88cm.) and non-diabetic subjects age between 30- 60 years was carried out. Fasting plasma glucose, fasting insulin and lipid profile were done. Insulin sensitivity and secretory status was calculated using homeostasis model assessment (HOMA) software (HOMA%S, HOMA%B and HOMA-IR). The subjects were divided into two groups according to their lipid status (128 normolipidemic and 118 hyperlipidemic) and their insulin sensitivity was compared. Results: The hyperlipidemic subjects showed substantially lower insulin sensitivity and higher insulin resistance in comparison to normolipidemic subjects. The mean of HOMA%S of hyperlipidemic and normolipidemic subjects were 80 and 155 (p<.0001) respectively. The mean of relative insulin resistance HOMA-IR was 2.66 in hyperlipidemic subjects which was 1.05 in normolipidemic subjects. Insulin secretory status (HOMA%B) oftwo group were 178 and 116 respectively. Conclusion: Insulin sensitivity of otherwise healthy non-obese hyperlipidemic subjects is lower than normolipidemic subjects. The B cells of hyperlipidemic subjects have to work more to compensate lowered insulin sensitivity.